Maternal Fetal Attachment among Pregnant Women Attending in a Provincial Hospital - Sapkota, Sumitra; Thapa Pandey, Bandana (Journal of Nursing Education of Nepal, 2024)
Introduction: Maternal-fetal attachment (MFA) refers to the behaviors and emotions exhibited by expectant mothers toward their unborn child including care, commitment, and nurturing actions. The maternal psychological state encompassing thoughts, behaviors, and emotions significantly influences fetal development by promoting healthier self-care and pregnancy-related health practices. The main objective of this study was to assess maternal-fetal attachment among first-time pregnant women attending antenatal care at a provincial hospital in Hetauda, Nepal.Methods: a descriptive cross-sectional study was conducted among first-time pregnant women attending antenatal care at a provincial hospital in Hetauda, Nepal. Data were collected using a structured two-part questionnaire comprising a socio-demographic and obstetric profile and the validated Cranley Maternal-Fetal Attachment Scale. Descriptive and inferential statistics were performed by using SPSS.Results: Among 145 participants, 80.7% demonstrated a high level of maternal-fetal attachment, with a mean total score of 85.32. Among the five domains of the Cranley scale, “giving of self” showed the highest mean score (4.31 ± 0.50), while “interaction with fetus” scored the lowest (2.78 ± 0.96). Statistically significant associations were observed between MFA scores and maternal age (p < 0.003), educational status of the respondent and her husband (p < 0.001), timing of antenatal care initiation, emotional response to ultrasound, and family support (p < 0.000).Conclusion: Most first-time pregnant women in this study exhibited high maternal-fetal attachment. Factors such as education, age, antenatal clinic timing, emotional experiences, and support systems significantly influenced attachment levels. These findings emphasize the importance of integrating psychological support into routine antenatal care to ensure comprehensive maternal well-being.
Keywords: Pregnant women; maternal fetal attachment